The harvest of Medieval theology Gabriel Biel and late Medieval nominalism - Oberman, Heiko Augustinus (Grand Rapids, MI Baker, 2000)
Includes bibliographical references and indexes.
First ed. published 1963
Keywords: Theology, doctrinal -- history -- Middle Ages, 600-1500.; Religious thought -- Middle Ages, 600-1500.